1996
DOI: 10.1016/0885-3924(95)00205-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pain practices: A national survey of health professionals

Abstract: The purpose of this study was to examine how health-care providers in U.S. teaching hospitals assess and manage children's pain. A 59-item questionnaire was sent to institutions with pediatric residency programs listed in the 1992 National Residency Matching Program. Two hundred and twenty-seven questionnaires were sent and 113 were returned. Two-thirds were from nurses, one-third from physicians. Sixty percent of the respondents stated that they had standards of care or protocols for pain in their institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 8 publications
6
43
0
2
Order By: Relevance
“…On the contrary, an unsatisfactory percentage of correct answers resulted concerning the treatment of pain in children. This data confirms what has been reported in other surveys regarding the treatment of pain in children, and two explanations are plausible: pain in children is often underestimated and undertreated [3,14,16]; children in pain, especially if affected by cancer, are generally treated in dedicated departments and, consequently, general radiotherapists rarely treat children. No major statistical differences regarding age, position, region of residence, availability of consultants, and colleagues with main interest in palliative care have been registered.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, an unsatisfactory percentage of correct answers resulted concerning the treatment of pain in children. This data confirms what has been reported in other surveys regarding the treatment of pain in children, and two explanations are plausible: pain in children is often underestimated and undertreated [3,14,16]; children in pain, especially if affected by cancer, are generally treated in dedicated departments and, consequently, general radiotherapists rarely treat children. No major statistical differences regarding age, position, region of residence, availability of consultants, and colleagues with main interest in palliative care have been registered.…”
Section: Discussionsupporting
confidence: 92%
“…Respondents in Fuller and Conner's (1997) study stated that they learnt to assess pain &dquo;on the job&dquo;. Broome et al, (1996) found that the nurses in their study felt that a knowledge deficit was an obstacle to adequate pain management thereby corroborating the findings outlined above. Francke et al, (1996) state many nurses feel a need for continuing education about pain management.…”
supporting
confidence: 58%
“…Temel hemşirelik eğitiminde farmakolojik olmayan yöntemler öğretilmektedir ancak hemşireler bu yöntemleri pratikte çok az gözlemledikleri ya da yaptıkları için bilgilerini unutmuş olabilirler. Farmakolojik olmayan yöntemlerin ağrı kontrolünde kullanılması gerektiği özellikle son yıllarda hem ders kitaplarında hem de çalışmalarda vurgulanmaktadır [6,7] Farmakolojik olmayan yöntemlere ilişkin yapılan çalışmalarda, bu yöntemlere ilişkin hemşirelerin ciddi bilgi eksikliklerinin olduğunu göstermektedir [26][27][28][29].…”
Section: Discussionunclassified